Hydrological changes in the lower part of Mesopotamian Basin - AL-Mahmood, Hassan K. H. (Iraqi Journal of Aquaculture, 2021)
This study was examined the hydrological changes in the water ways for the and the marshes associated with them in Southern part of lower Mesopotamian catchment area (Tigris and Euphrates Rivers and their branches in Amarah, Nasiriyah and Basra ) and the main tributaries of the Shatt al-Arab River( Swaib, Garmat Ali and Karun ), and the significant changes in the overall hydrological conditions of water discharge and water quality. Water discharge and water samples were collected quarterly for four sites during 2011, the laboratory analysis were performed to determine physical and chemical characteristics at these sites. Results shows that the quarterly water discharge rate in Tigris River is seasanal 41.05 m3/s at Qalaat saleh, Euphrates River at Chabaish 11.65 m3/s, Shatt Al-Arab River in Qurna 39.65m3/sec, that the Garmat Ali to cause the loss of an average of 20.1 m 3 / sec from Shatt al-Arab water into to Hor Alhammar, during a seasonal fluctuation between summer and winter, causes water relapsing during the winter water Contamination of the central part of the Shatt al-Arab. Clear water shortage reflected on water quality in Southern Iraqi Rivers and their branches. While water salinity is ranging between 1.31-1.42 gm/l in Tigris River, 3.46-5.15 gm/l in Euphrates River, 2.00-2.29 gm/l in Garmat Ali River, 1.00 -1.98 gm/l in Ezz River and 1.59-1.83 gm/l in Shatt al-Arab River . This study shows that the Tigris and Euphrates Rivers suffer of large water scarcity and lack of supply from Swaib and Garmat Ali Rivers to the Shatt al-Arab, as well as stop the flow of Karun River to the Shatt al-Arab and wasting a large portion of water from the Tigris and Euphrates Rivers to restore some parts of Southern Iraqi marshes. the contribution of the Euphrates River in the salinity of the Shatt al-Arab 50% during the winter, Although the total discharge does not exceed 25% , and the contribution of the Garmat Ali 30% and 20% of the Tigris River, while the effect of the salt of the Tigris River 100 % during the summer. The study concludes that the hydrological situation in the study area is continuous deterioration due to absence of any instant or far-reaching strategies to handle this deterioration, which calls for the intensification of future studies in various disciplines related to water resources management.